Pengaruh Kombinasi Latihan Senior Elastic Band (SEB) dan Terapi Musik Religi Terhadap Penurunan Tekanan Darah pada Pasien Hipertensi di Desa Bangeran Kecamatan Dukun Kabupaten Gresik - Muhammad Masyhuri; Virgianti Nur Faridah; Trijati Puspita Lestari (Lembaga Pengembangan Kinerja Dosen, 2024)
Severe hypertension in the country is many. One effort can be made with non-pharmacological therapies in which practice is Senior Elastic Band Exercise in combination with religious music therapy. The purpose of this research is to know how a combination of Senior Elastic Band (SEB) exercise and religious music therapies affect a drop in blood pressure on hypertensive patients in Bangeran Village, Dukun District, Gresik Regency. The design of this research uses pre-experimental, with a sample of 35 people taken consecutive samples. A combination of practice and religious music therapy is performed twice a week for 20 minutes each exercise. Research instruments using sphygmomanometer, observation sheet blood pressure and SOP. The data analyzed is pre intervention 1 and the post data intervention 2 uses the wilcoxon test. Studies show that action can affect drop in blood pressure before and after action with a value of p= 0,000 (p<0.05) against a systolic 13.43 mmHg and diastolic 6.54 mmHg. SEB exercises can improve flexibility, fitness, promote blood circulation and improve vascularization of lower blood pressure. Exposure to religious music causes the body to relax so that the heart pumps slower and there will be a drop in blood pressure. The POSBINDU of bangeran village need to take precautions non-pharmacological hypertension besides doing pharmacological treatment.